2004
DOI: 10.1097/01.bsd.0000112049.36255.bc
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Computed Tomography in Assessing Thoracic Pedicle Screw Malposition

Abstract: Computed tomography was found to be relatively insensitive in assessing thoracic pedicle screw position. In the face of postoperative complications, surgical exploration and hardware removal may still be necessary despite negative computed tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Extensive literature has been published describing the technique, benefits, and drawbacks of each method, as well as comparisons between different approaches. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] With its increasing use has come a multitude of studies regarding the safety of this technique. Proper screw placement is imperative in order to avoid complications such as CSF leak, and pedicle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Extensive literature has been published describing the technique, benefits, and drawbacks of each method, as well as comparisons between different approaches. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] With its increasing use has come a multitude of studies regarding the safety of this technique. Proper screw placement is imperative in order to avoid complications such as CSF leak, and pedicle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…In a study presented by Fayyazi and colleagues using a simple "in" or "out" classification for pedicle screw placement, the authors found a fair to moderate degree of interobserver and intraobserver agreement using CT and the kappa statistic [7]. The authors of that study, using cadaveric specimens to compare the accuracy of CT with open dissection, concluded that assessment beyond axial CT may be necessary.…”
Section: Discussionmentioning
confidence: 94%
“…Advances in imaging have led to computed tomography (CT) image assessment methods being regarded as the current gold standard in evaluating in vivo pedicle screw placement success [7,15]. When compared with radiographs, CT image-based evaluations have been reported to improve accuracy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Routine anteroposterior and lateral views are inadequate to evaluate screw position 23,24 . CT is the most accurate study; however, its sensitivity and specificity varied from 76% to 86% and 75% to 88%, respectively [25][26][27] . Inferior wall violations are the most difficult to detect on CT scans 25 .…”
Section: Discussionmentioning
confidence: 99%
“…CT is the most accurate study; however, its sensitivity and specificity varied from 76% to 86% and 75% to 88%, respectively [25][26][27] . Inferior wall violations are the most difficult to detect on CT scans 25 . It is our opinion that the only way to accurately demonstrate a satisfactory placement of thoracic screws is using postoperative CT scans; medial and lateral violations can be easily seen with this technique.…”
Section: Discussionmentioning
confidence: 99%